The (G′/G)-Expansion Method and Its Application for Higher-Order Equations of KdV (III) - Huizhang Yang; Wei Li; Biyu Yang (Journal of Applied Mathematics)
New exact traveling wave solutions of a higher-order KdV equation type are studied by the (G′/G)-expansion method, where G=G(ξ) satisfies a second-order linear differential equation. The traveling wave solutions are expressed by the hyperbolic functions, the trigonometric functions, and the rational functions. The property of this method is that it is quite simple and understandable.